MENILIK SIKAP BAHASA MAHASISWA UNIVERSITAS BRAWIJAYA: UPAYA PENEGUHAN BAHASA INDONESIA MENUJU INTERNASIONALISASI BAHASA - Trisna Andarwulan; Aswadi Aswadi (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
This research is based on the researcher concerned as a lecture of Bahasa Indonesia in University of Brawijaya (UB). The researcher found out that student’ pride when speaking Bahasa Indonesia is low. This condition will become concern the position of Bahasa Indonesia itself since language attitude is one of the critical factors of language learning. Therefore, this research aimed to describe (a) Students’ language attitude towards Bahasa Indonesia and (b) Students’ language attitude in strengthen Indonesian language skill as an effort toward international language. This research using descriptive method with quantitative approach. The research population was students of UB academic year 2017. The sample carried out with random sampling technique to 60 students from the field of exact sciences and social. The result showed that UB students’ language attitude towards Bahasa Indonesia is still low. Not all students have a positive attitude towards Bahasa Indonesia. The awareness that language is part of the identity needs to be improved to create positive attitude that refers to language appeal and pride of a language speaker.